The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/bjophthalmol-2013-304660
|View full text |Cite
|
Sign up to set email alerts
|

Topical antibiotics for the management of bacterial keratitis: an evidence-based review of high quality randomised controlled trials

Abstract: Results of this review suggest no evidence of difference in comparative effectiveness between fluoroquinolones and aminoglycoside-cephalosporin treatment options in the management of BK. There were differences in safety profile, however. Fluoroquinolones decreased the risk of ocular discomfort and chemical conjunctivitis while ciprofloxacin increased the risk of white corneal precipitate compared with aminoglycoside-cephalosporin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 39 publications
1
68
0
7
Order By: Relevance
“…The authors found no significant difference in the relative risk of treatment success defined as complete re-epithelialization of the cornea or on time to cure. 30 While there was an increase in the relative risk of minor adverse events such as ocular discomfort or chemical conjunctivitis with aminoglycoside-cephalosporin compared with fluoroquinolones, there was no difference in serious complications. 3033,34 …”
Section: Bacterial Keratitismentioning
confidence: 95%
“…The authors found no significant difference in the relative risk of treatment success defined as complete re-epithelialization of the cornea or on time to cure. 30 While there was an increase in the relative risk of minor adverse events such as ocular discomfort or chemical conjunctivitis with aminoglycoside-cephalosporin compared with fluoroquinolones, there was no difference in serious complications. 3033,34 …”
Section: Bacterial Keratitismentioning
confidence: 95%
“…While awaiting cultures, empiric treatment should be started immediately and the antibiotic chosen should be of sufficiently broad spectrum to cover likely pathogens based on local bacterial prevalence and antibiotic susceptibilities. [2] Since regional differences exist in the etiologies of bacterial keratitis[3,4], good local epidemiological data are needed for better empirical treatment of bacterial keratitis.…”
Section: Introductionmentioning
confidence: 99%
“…Dolayısıyla oküler yüzeye ciddi toksik etki gösterirler. 6 Kuru göz hastalarında bu durum hem azalmış yıkama etkisi hem de azalmış epitelyotrofik faktörler (epidermal büyüme faktörü, fibronektin, vitamin A, nörotrofik büyüme faktörleri) nedeni ile daha belirgindir. Bu hastalarda sadece suni gözyaşı desteği yeterli olmayabilir ve bu aktif komponentlerin replasmanı gerekebilir.…”
Section: Discussionunclassified